Candlenut Shell and Clay-Derived Monoliths with Molasses Binder: A Sustainable Approach to Water Dye Decontamination - Farid Nanda; Darmadi Darmadi; Muhammad Zaki; Adisalamun Adisalamun; Aula Chairunnisak (Jurnal Kimia Sains dan Aplikasi, 2025)
This study presents a sustainable approach to water dye decontamination using monoliths constructed from candlenut shells, clay, and molasses as a binder. The candlenut shells were activated to form carbon and then mixed with natural clay and molasses to create the monolith composite. The dough was pushed through a stainless-steel mold featuring seven circular openings, each measuring 2 cm in width and 2 cm in thickness, to create the monoliths (MCC and MMCC). The monoliths were rigorously tested for adsorption efficiency, isotherm behavior, and kinetic properties. Results showed a high dye removal efficiency, with 92% for methylene blue and 74% for methyl orange, which was attributed to the stronger interaction of methylene blue with the negatively charged surface of the monoliths. The isotherm analysis followed the Langmuir model, indicating monolayer adsorption on uniform active sites. Kinetic studies using linear regression analysis aligned with the pseudo-second-order model, indicating that chemical adsorption was the controlling factor in the rate. Characterization of the monoliths using Scanning Electron Microscopy (SEM) revealed a porous surface morphology, while X-ray Diffraction (XRD) identified the crystalline structures present. Fourier Transform Infrared Spectroscopy (FTIR) confirmed the presence of functional groups essential for dye adsorption, and Brunauer-Emmett-Teller (BET) analysis determined the specific surface area and pore size distribution. In conclusion, this study underscores the viability of using candlenut shell and clay-derived monoliths as efficient and environmentally friendly adsorbents for wastewater treatment, providing a practical solution to dye pollution.